IMPLEMENTASI ALGORITMA NAÏVE BAYENSIAN DALAM MENENTUKAN JURUSAN DI SMU (STUDI KASUS SMU MUHAMMADIYAH ENREKANG) - Rismawati; Satriawaty Mallu (P3M STMIK Profesional Makassar, 2013)
Naive Bayensian Algorithm Implementation In The Determination Of Department In High School (Case Study : Muhammadiyah High School Enrekang District of South Sulawesi Province), The purpose of the majors is that later in life lessons that will be given to students to be more focused because it was in accordance with their interests. The teachers BK/BP since the distant days usually have done so potential students' psychological psychologically more unearthed and majors that would have done no wrong direction. However, many parents who make children entering science majors. Though the majors have decided the school through teacher meetings. So, when a student scores less than the standards set then he should go majoring in social studies or English. In school education, the differences of each student must be considered because it can determine whether the poor student achievement. Issues discussed in this study is how to design system-based decision support technology to help high school students in choosing majors that match the capabilities, interests, talents and personality.